69.4k views
5 votes
Inverse Function In Exercise,analytically show that the functions are inverse functions.Then use the graphing utility to show this graphically.

f(x) = e^2x-1
g(x) = 1/2 + In(x)1/2

User Clweeks
by
5.3k points

1 Answer

3 votes

Answer:


f^(-1)(x)=g(x)=\frac{\text{ln}(x)}{2}+(1)/(2)

Explanation:

Please find the attachment.

We have been given two functions as
(x)=e^(2x-1) and
g(x)=(1)/(2)+\frac{\text{ln}(x)}{2}. We are asked to show that both functions are inverse of each other algebraically and graphically.

Let us find inverse function of
f(x)=e^(2x-1) as:


y=e^(2x-1)

Interchange x and y values:


x=e^(2y-1)

Take natural log of both sides:


\text{ln}(x)=\text{ln}(e^(2y-1))


\text{ln}(x)=(2y-1)*\text{ln}(e)


\text{ln}(x)=(2y-1)*1


\text{ln}(x)=2y-1


\text{ln}(x)+1=2y-1+1


\text{ln}(x)+1=2y


\frac{\text{ln}(x)+1}{2}=(2y)/(2)


\frac{\text{ln}(x)}{2}+(1)/(2)=y


f^(-1)(x)=\frac{\text{ln}(x)}{2}+(1)/(2)

Therefore, we can see that function
g(x)=(1)/(2)+\frac{\text{ln}(x)}{2} is inverse of function
f(x)=e^(2x-1).

We can see that both functions are symmetric about line
y=x, therefore, both functions are inverse of each other.

Inverse Function In Exercise,analytically show that the functions are inverse functions-example-1
User Kevz
by
4.3k points